Environmental Sustainability: Mediating Effect of Environmental Knowledge for Pro-Environmental Behaviour - Noor, Nurul Hidayana Mohd; Zaini, Syeliya Md; Pudini, Susan; Sidek, Mohammad Syazwi Jaafar (Indonesian Journal of Sustainability Accounting and Management, 2024)
This study aims to examine the level of pro-environmental behaviour based on demographic profile and the interrelationship between environmental connectedness and pro-environmental behaviour via the mediating role of environmental knowledge. The quantitative and convenience sampling collected data from the Malaysian public. The collected data were analysed using the descriptive statistics and structural equation modelling (SEM) method. The findings show that there is a significant degree of pro-environmental conduct. Interestingly, though, there is very little variation in pro-environmental activity by age, gender, or educational attainment. Subsequently, the SEM findings demonstrated that environmental connectivity strongly impacted pro-environmental conduct. Additionally, environmental knowledge considerably and partially mediated the association between environmental connectedness and pro-environmental behaviour. This paper suggests that values and behavioural norms influence individual pro-environmental behaviour. This study suggests that people’s backgrounds, such as family upbringing, parenting lessons and school syllabuses, are crucial in shaping the young generation and the adults towards pro-environmental behaviour. Therefore, the government and local authorities can encourage parents and peers to nurture their children’s environmental values and perceived behaviour for better environmental sustainability. The value of the study shows that individuals’ values, behaviour and attitudes towards the environment can be inculcated at home and need continuous practice anywhere.